Research on adaptive iterative decoding algorithm based on LDPC/Turbo dual-mode decoder - Wang, Xiumin; Hong, Fangfei; Yin, Haibing; Li, Zhengquan; Xiao, Binggang (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2016)
In view of the shortcoming that the design of LDPC/Turbo dual-mode decoder does not fully consider the precise calculation of iteration number, we propose a adaptive iterative decoding algorithm which is suitable for LDPC and Turbo codes. The algorithm is used to calculate the error probability by tracking the middle messages, and to calculate the number of iterations according to multi-conditions, thus we can achieve the self-adaptability of the variation of the decoding algorithm according to the error probability. We reduce the average number of iterations by applying an improved predecision mechanism, and build the test link of WIMAX system on Matlab platform to test the relationship between the BER performance of the multi-algorithms and iteration number, and implement the LDPC/Turbo dual-mode decoder with 12 SISOs parallel processing units. The result shows that the design of the decoder fully satisfies the requirement of the maximum code length under the standard, and can reduce the redundant iterative